Assessment of Eucalyptus seedlings grown in biodegradable containers and their growth in clonal plantations - Vitor S. Brito; Emanuela F. Gama-Rodrigues; José L. M. Gonçalves; Alexandre V. Ferraz; José C. A. Júnior (New Forests, 2026)

Forest residue removal undermines soil health and micronutrient transfer to trees, compromising sustainable productivity of Eucalyptus plantations - Antonio L. Florentino; Nariane de Andrade; Nikolas S. Mateus; Bruna E. Schiebelbein; Adam C. Rodrigues; Liamara S. Masullo; Alexandre V. Ferraz; Eduardo Mariano; Fernando D. Andreote; Carlos E.P. Cerri; Maurício R. Cherubin; Timothy R. Filley; et al. (Soil and Tillage Research, 2026)

Twelve-year residual effect of sewage sludge on the biogeochemical cycling of potentially toxic elements in tropical Eucalyptus plantation - Antonio L. Florentino; Alexandre V. Ferraz; Adam C. Rodrigues; Nikolas S. Mateus; Paulo H.S. Cardoso; Timothy R. Filley; Eduardo Mariano; José Lavres; José L.M. Gonçalves; Cassio H. Abreu-Junior (Forest Ecology and Management, 2025)

Coral bleaching and mortality across a 24° latitudinal range in the Southwestern Atlantic during the fourth global bleaching event - Miguel Mies; Giovanna Destri; Carlos H. F. Lacerda; Júlia L. M. Carvalho; Júlia Y. Ibanhez; Arthur Z. Güth; André L. Luza; Luiza P. Campos; Aline C. Shimada; Kenzo N. T. Omaki; Bianca E. Jahn; Yasmim A. Abreu; et al. (Coral Reefs, 2025)

Long distance pollen dispersal and intrapopulation genetic structure determined by clonal diversity in Hymenaea stigonocarpa populations of the Brazilian savanna - Maria A. Moreno; David Boshier; Roberto Tarazi; Evandro V. Tambarussi; Bruna I. Aguiar; Elza M. Ferraz; Paulo Y. Kageyama; Alexandre M. Sebbenn (Trees, 2022)

ATLANTIC ANTS: a data set of ants in Atlantic Forests of South America - Rogério R. Silva; Felipe Martello; Rodrigo Machado Feitosa; Otávio Guilherme M. Silva; Lívia Pires do Prado; Carlos Roberto F. Brandão; Emília Zoppas de Albuquerque; Maria Santina C. Morini; Jacques Hubert Charles Delabie; Erison Carlos dos Santos Monteiro; Agripino Emanuel Oliveira Alves; Alexander L. Wild; et al. (Ecology, 2022)
Ants, an ecologically successful and numerically dominant group of animals, play key ecological roles as soil engineers, predators, nutrient recyclers, and regulators of plant growth and reproduction in most terrestrial ecosystems. Further, ants are widely used as bioindicators of the ecological impact of land use. We gathered information of ant species in the Atlantic Forest of South America. The ATLANTIC ANTS data set, which is part of the ATLANTIC SERIES data papers, is a compilation of ant records from collections (18,713 records), unpublished data (29,651 records), and published sources (106,910 records; 1,059 references), including papers, theses, dissertations, and book chapters published from 1886 to 2020. In total, the data set contains 153,818 ant records from 7,636 study locations in the Atlantic Forest, representing 10 subfamilies, 99 genera, 1,114 ant species identified with updated taxonomic certainty, and 2,235 morphospecies codes. Our data set reflects the heterogeneity in ant records, which include ants sampled at the beginning of the taxonomic history of myrmecology (the 19th and 20th centuries) and more recent ant surveys designed to address specific questions in ecology and biology. The data set can be used by researchers to develop strategies to deal with different macroecological and region‐wide questions, focusing on assemblages, species occurrences, and distribution patterns. Furthermore, the data can be used to assess the consequences of changes in land use in the Atlantic Forest on different ecological processes. No copyright restrictions apply to the use of this data set, but we request that authors cite this data paper when using these data in publications or teaching events.

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Responses of coppiced Eucalyptus to macro- and micronutrient application - José Henrique T. Rocha; Andréa V. A. Wenzel; Eduardo A. S. C. Melo; Ângela Simone Freitag Lima; Rodrigo Eiji Hakamada; Alexandre de Vicente Ferraz; José Carlos Arthur Junior; José Leonardo de Moraes Gonçalves; Gabriela Moreira; Antônio Natal Gonçalves (New Forests, 2019)

ATLANTIC BIRDS : a data set of bird species from the Brazilian Atlantic Forest - Érica Hasui; Jean Paul Metzger; Rafael G. Pimentel; Luís Fábio Silveira; Alex A. d. A. Bovo; Alexandre C. Martensen; Alexandre Uezu; André L. Regolin; Arthur Â. Bispo de Oliveira; Cassiano A. F. R. Gatto; Charles Duca; Christian B. Andretti; et al. (Ecology, 2018)
South America holds 30% of the world's avifauna, with the Atlantic Forest representing one of the richest regions of the Neotropics. Here we have compiled a data set on Brazilian Atlantic Forest bird occurrence (150,423) and abundance samples ( N = 832 bird species; 33,119 bird individuals) using multiple methods, including qualitative surveys, mist nets, point counts, and line transects). We used four main sources of data: museum collections, on‐line databases, literature sources, and unpublished reports. The data set comprises 4,122 localities and data from 1815 to 2017. Most studies were conducted in the Florestas de Interior (1,510 localities) and Serra do Mar (1,280 localities) biogeographic sub‐regions. Considering the three main quantitative methods (mist net, point count, and line transect), we compiled abundance data for 745 species in 576 communities. In the data set, the most frequent species were Basileuterus culicivorus , Cyclaris gujanensis , and Conophaga lineata . There were 71 singletons, such as Lipaugus conditus and Calyptura cristata . We suggest that this small number of records reinforces the critical situation of these taxa in the Atlantic Forest. The information provided in this data set can be used for macroecological studies and to foster conservation strategies in this biodiversity hotspot. No copyright restrictions are associated with the data set. Please cite this Data Paper if data are used in publications and teaching events.

Effect of reproductive methods and GnRH administration on long-term protocol in Santa Ines ewes - Marcos V Biehl; Marcos V C Ferraz Junior; Evandro M Ferreira; Daniel M Polizel; Alexandre A Miszura; José P R Barroso; Gabriela B Oliveira; Analisa V Bertoloni; Alexandre V Pires (Tropical Animal Health and Production, 2017)